THE USE OF LETTERLAND STRATEGIES IN TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS - Julianti . .; Rahmad . Husein; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2021)
The purpose of this research was to help teachers to enrich their knowledge about Letterland strategies in teaching English vocabulary to young learners. The objective of this research was to investigate the types of problem faced by teachers while using Letterland strategies. This research applied descriptive qualitative design and the data gathered from the sentences of four teachers in Nursery class at a Singapore Pre-School, Medan. The techniques of collecting data were observation and interview. Then, the techniques in analyzing the data were condensation, data display, and conclusion drawing/verification. Based on the data analysis, it was found that there were two types of problem faced by all the teachers; an internal disturbance (54.55%),  and an external disturbance (45.45%). It was concluded that Letterland strategies were good for young learners in learning English vocabulary because it provided some fun activities that contained of multi-sensory based learning which they were able to see, hear, do, and touch it.         Keywords: English Vocabulary; Letterland Strategies; Young Learners